Down‐regulated FOXA1 in early‐onset pre‐eclampsia induces apoptosis, and inhibits migration and invasion of trophoblast cells. (1st October 2020) - Zhu, Juan; Wei, Yunjian; Wang, Zhen; Jie, Qiuling; Sun, Fei; Li, Qi; Long, Ping; Huang, Yuanhua; Yu, Yanhong; Ma, Yanlin
Abstract: Background: Pre‐eclampsia (PE) is a major cause of maternal and neonatal mortality and morbidity. Abnormal invasion of trophoblast cells is a major pathogenesis observed in PE. In the present study, we aimed to explore the association between forkhead box A1 (FOXA1) and early‐onset pre‐eclampsia (EOPE) and to determine the effects of FOXA1 on trophoblast cell apoptosis, migration and invasion. Methods: Clinical data and placentas of patients with EOPE and normal pregnant women were collected in the First Affiliated Hospital of Hainan Medical College. The protein expression levels of FOXA1 in the clinical samples were evaluated by western blotting and immunohistochemistry. The effects of FOXA1 knockdown on HTR‐8/SVneo cell apoptosis, migration and invasion were evaluated by flow cytometry, wound healing and transwell invasion assays, respectively. Results: The western blot and immunohistochemical analysis showed that FOXA1 protein expression in placenta of EOPE group was significantly lower than that of normal group. The expression of FOXA1 in the placentas of EOPE and normal pregnant women was negatively correlated with systolic pressure and diastolic pressure. The expression of FOXA1 in EOPE and normal pregnant women was positively correlated with gestation weeks at delivery and neonatal birthweight. In vitro functional studies showed that silencing FOXA1 increased apoptosis, and inhibited the migration and invasion of HTR‐8/SVneo cells. Conclusions: Down‐regulation of FOXA1 in the placentas may indicate poor prognosis of EOPE. Silencing of FOXA1 induced apoptosis in trophoblast cells, and impaired the migratory and invasive capacity of trophoblast cells. FOXA1 may represent a potential therapeutic target for EOPE. Abstract : Representative photomicrography of placental histopathology in the normal pregnant group and the early‐onset pre‐eclampsia (EOPE) group. Forkhead box A1 protein expression in placenta of EOPE group was significantly lower than that of the normal group.